Pemodelan Ontologi Web Semantik pada Pencarian Lowongan Pekerjaan Berdasarkan Profil Pencari Kerja - Yunita, Yunita (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2017)
Abstract Ontology represents knowledge about the meaning of the object, the property of an object, and the relation between those objects that may occur in the knowledge domain. Before the development of semantic web technology, most applications that use web technology today still use relational database as a representation of stored data. Relational databases have some disadvantages, especially in terms of storage and relationships between complex data. This study aims to design an ontology which is a metadata of semantic web-based applications used for job search based on job seeker profile ie GPA, skill, and education. Semantic web technology uses the ontology used to represent knowledge. In a job search ontology based on this job seeker profile, an instance is performed using the Protégé version 5.0 beta editor.Keywords-ontology, searching, job search, semantic web, protege